Investigation of Enterotoxigenic Coagulase-negative Staphylococci Isolated from Local and Imported Dairy Products; a Microbiological Study - Ali, Niyaz Sirwan; Arif, Huner Hiwa (Kurdistan Journal of Applied Research, 2020)
Coagulase negative staphylococci (CNS) have been recorded as a conveying vector for virulence genes and have been implicated in some cases of food poisoning. Research interest in CNS has increased over the past decade following their implication in infections in animals and humans. This study was aimed to detect CNS isolated from 150 dairy products (yoghurt, several types of cheese, Lork, and Serezh) in Sulaimani and Halabja governorate. Thirteen isolates out of 150 samples were identified as CNS using the VITEK® 2 system as an identification method. Results revealed that the most common isolates species including Staphylococcus saprophyticus, Staphylococcus sciuri and Staphylococcus xylosus each species have been identified in 3 samples separately (23%), followed by Staphylococcus vitulinus was in 2 samples (15%), Staphylococcus equorum found in 1 sample (8%), and Staphylococcus gallinarum also was in one sample (8%). The isolated CNS did not have enterotoxins type A to E according to RIDASCREEN kit test. Studying the growth limits of S. saprophyticus and S. vitulinus results showed that S. saprophyticus grew better at pH levels (5,6,7) at (25?,37?) and low NaCl concentration (5%), while low bacterial activity was observed at pH 4 at all temperatures and NaCl concentrations and also at 4? at all pH and NaCl levels. S. vitulinus behaviour was almost the same as S. saprophyticus but, S. vitulinus was able to tolerate different NaCl concentrations and overall had higher bacterial activity in all parameter’s interactions than S. saprophyticus. Investigating the effect of acetic acid and lactic acid on the growth of previous species where studied, S. saprophyticus grew better in different concentrations of L.A but S. vitulinus showed more activity than S. saprophyticus in A.A and the growth of both species inhibited at 0.4% of L.A at the first 24 hours of incubation.